(untitled) (International Seven Journal of Multidisciplinary, 2023)
The aging of the Brazilian population is a reality that has been noticed for some decades and that tends to become even greater over the years. When aging results in senility, family members often need to shelter the elderly in Long-Term Care Institutions (LTCFs), in which the loss of the uniqueness of individuals may occur. In this context, it is of great importance for nurses to know the reality of the elderly, from their own point of view. Objective: To understand the feelings and perceptions presented by elderly residents of two LTCFs in the west of the state of São Paulo. Method: Descriptive, exploratory research with a qualitative approach. The research subjects were seven elderly residents of two LTCFs in the west of the state of São Paulo. Data were collected through recorded and transcribed interviews, which were later analyzed according to thematic content analysis, raising two thematic categories: 1) Feelings related to personal history and 2) Impressions regarding relationships in the LTCF. Results: The feelings identified in the speeches were especially loss, loneliness, worthlessness, and guilt. Regarding the LTCFs, feelings of satisfaction and dissatisfaction emerged. Final Considerations: The perceptions arising from the analysis of the results can promote reflections in LTCF professionals and managers. It is also important that the working teams can be composed of diverse professionals who are able to meet the needs faced by the institutionalized elderly.